Probiotics survival, antioxidant activity and sensory properties of yogurt flavored with herbal essential oils - Azizkhani, M. (2023)
The objective of this study was to investigate the viability of the probiotics, antioxidant activity and organoleptic acceptability of probiotic-yogurt containing essential oils (peppermint, basil and zataria). Samples were produced using probiotic organisms Lactobacillus acidophilus LA5, Lactobacillus fermentum and Bifidobacterium Bb-12 besides the starter culture and added essential oils. The presence of essential oils did not affect LA5 population in yogurt during 4 weeks of storage but the growth of Bb12 was retarded. Water extract of zataria-yogurt showed the highest inhibitory effect on DPPH radicals followed by peppermint and basil samples. Peppermint yogurt received the highest score followed by basil and control yogurt but zataria sample did not reach the consumer acceptability limit (score >5). The present findings suggest that adding zataria, basil or peppermint essential oils into probiotic yogurt formulation improves the antioxidant potential of the product. Peppermint and basil samples showed both good antiradical activity and sensory acceptability.